Characteristic of the material deposits, microclimate profile, epiphyte abundance, and bacteria populations in the above-ground ecosystem of oil palm (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Pradiko I, Farrasati R, Rahutomo S, Sapalina F, Pane RDP, Hidayat F, Ginting EN. 2022. The physical, chemical, and biological characteristics of microhabitats inside oil palm trunk axils in North Sumatra, Indonesia. Biodiversitas 23: 3793-3807. Above-ground ecosystems (AGE) components in oil palm plantations consist of epiphytic plants and fauna in microhabitat within the axil of pruned fronds. This research aimed to identify the characteristics of microhabitat, including microclimate profile, physical and chemical properties of the material deposit, epiphyte abundance, and microbe population. The study sites were located in the eastern and western regions of North Sumatra. Furthermore, vertical observations were taken on oil palm trunks at the height of 20, 100, 150, 200, and 300 cm. The study indicated that the microclimate, nutrients content, physical properties of the material deposit, and bacterial populations in the trunk axils of oil palm in the eastern differed from the western region. There was no obvious pattern in the microclimate profile for individual oil palms. However, there was a change in N, C-organic, and C/N ratios with the increasing height of microhabitat sites. In terms of abundance, Nephrolepis bisserata and Vittaria ensiformis epiphytes were more dominant in the upper and bottom trunk, respectively. The microhabitat at the bottom trunk had a denser bacterial population, negatively correlated with N, C-organic, C/N ratio, Mg, and pH.